Free radical polymerization of acrylates bearing acetylene for preparation of clickable polymers. (16th July 2021) - Zhang, Zhengyuan; Liu, Yu; Shui, Xiaochuan; Yu, Youqing; Zheng, Chunyan; Wang, Yuechuan
Abstract: It is still a challenge to directly, without any control means, synthesize polymers bearing acetylene groups by normal free radical polymerization (FRP) of acetylenyl vinyl monomers, such as propargyl (meth)acrylates, because the reactive acetylene groups result in chain branching and gelation. Some propargyl acrylates with alkyl substitutes, however, can afford linear and soluble polymers. To clarify the substitute effects the FRP behaviours of a series of acrylates bearing acetylene groups with or without substitutes are studied. Homopolymerizations of acetylenyl acrylates without or with mono-substitute on propargyl led to branched polymers at early reaction stage, and became gelled after 0.5 h with monomer conversion over 12% and gel content over 50%. The acetylenyl acrylates with di-substitutes on propargyl can afford linear and soluble homo- and copolymers with‾Mn up to over 10, 000 and with 45–75% monomer conversion, except for monomer 2-(2-methylbut-3-yn-2-yloxy)ethyl acrylate (DMPOEA) which has di-substitutes and a spacer connecting to the propargyl. Reactivities of vinyl and acetylene groups were found within 20 times difference by laser flash photolysis (LFP) experiments. The substitute effects of acetylenyl acrylates on FRP are explained by the intramolecular cycloaddition between CC and CC to form lactone from the s-cis conformers of the di-alkyl substituted acetylenyl acrylates. Propagating radicals can transform to stable allyl radicals by α-H atom transfer and thus the chain propagations stop. Both real-time FT-IR monitoring of photo-polymerization and high resolution 13 C NMR spectra of the polymer confirmed the existence of lactone units on polymer chains. The hypothesis is also accordance with facts obsorved in the FRP. Finally postpolymerization modification through acetylene groups on polymer chains by photo thiol-yne click reaction is exemplified. Graphical abstract: Image 1 Highlights: Substitutes on propargyl affect the free radical polymerization (FPR) of acetylenyl acrylate. The substitute effects on FPR were attributed to intramolecular cyclization to form lactone units. Clickable polymers with lactone and ethylene units were prepared from FRP of di-substituted acetylenyl acrylates.